Babesia sp. of the “South American Marsupialia Group”: First molecular detection in Didelphis albiventris (Didelphimorphia: Didelphidae) from Argentina - Sebastian, Patrick; Lamattina, Daniela; Vaschalde, Paula Josefina; Flores, Fernando Sebastián; Torrents, Jorgelina; Tarragona, Evelina Luisa (Elsevier, 2025)
Field captured specimens of Didelphis albiventris (Didelphimorphia: Didelphidae) from Formosa Province, Argentina, were analysed for possible infection with Babesia species. Whole blood samples of live-trapped D. albiventris were taken, genomic DNA was extracted and a Piroplasmida specific PCR assay targeting a fragment of the 18S rRNA gene was conducted. Positive PCR amplicon were sequenced and obtained DNA partial sequences were located in a phylogenetic context by constructing a maximum-likelihood tree. Two samples were positive and could be identified as Babesia species. Through phylogenetic analyses, both sequences were demonstrated to belong to a group of Babesia sp. associated with marsupials from Brazil and therefore previously defined as the “South American Marsupialia Group” (SAMG) of Babesia species. The results of this study represent the first report of a Piroplasmida species in a marsupial in Argentina. They further give an insight on the circulation of Babesia sp. in D. albiventris that, due to its synanthropic habits, plays an epidemiologically important role as potential hosts for emerging pathogens and ectoparasites of relevance in veterinary medicine.